PERBEDAAN PENGARUH PENDIDIKAN SEKS METODE SIMULASI DAN DISKUSI KELOMPOK TERHADAP SIKAPREMAJA PADA UPAYA PENCEGAHAN PERILAKU SEKS MENYIMPANG - Kumboyono, Kumboyono; M, Hanafi,; E. P, Lestari, (Fakultas Kedokteran Universitas Brawijaya, 2004)
Sex education is a process to express message that one of the purpose is to create adolescense positive attitude avoiding incorrect sex behavior. The method used to create adolescensepositive attitude in order to avoid the incorrect sex behavior are group discussion method, demonstration, playing role or simulation method. The purpose of this study was to find out the differences between the influence of giving sex education with simulation method and group discussion of adolescense attitude changes to avoid incorrect sex behavior, and to find out a method that give the biggest score of attitude changes amongthem. The design of this study was quasi experimental pretest posttest design. While the way to collect samples using multi stage random sampling technique with the number of 90 samples divided into 30 groups of control, 30 groups using simulation method of treatment and 30 groups using discussion group method of treatment. The result from showed that there was difference between score of pretest attitude and score of posttest attitude in the group of simulation treatment (t-test p = 0.644) and the discussion group of treatment (t-test p = 0.000), but there was no difference between score of pretest attitude and score of posttest in control group (t-test p = 0.000) α = 0.05. Another finding that there was difference attitude among control group, group of simulation treatment, and group of discussion treatment (anova p = 0.000) α = 0.05.